2011
DOI: 10.1007/s11606-011-1768-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cardiovascular Disease Prevalence on Women's Enrollment in Landmark Randomized Cardiovascular Trials: A Systematic Review

Abstract: Many studies have demonstrated that women are substantially underrepresented in cardiovascular trials, but few have considered that women develop cardiovascular disease at older ages than men. The extent to which observed gender enrollment inequalities persist after accounting for age-gender differences in disease prevalence is unknown. The purpose of the study was to compare observed rates of women participating in cardiovascular clinical trials with expected rates of female participation based on age-and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
3
21
1
Order By: Relevance
“…Stroke was not included in this analysis, however. 408 The percentage of women enrolled in recent stroke prevention trials of carotid disease and antiplatelet agents ranges from 25% to 53%, with an average of 34%, which is generally below the stroke prevalence rates by sex (Tables 14 and15).…”
Section: Representation Of Women In Stroke Clinical Trialsmentioning
confidence: 99%
“…Stroke was not included in this analysis, however. 408 The percentage of women enrolled in recent stroke prevention trials of carotid disease and antiplatelet agents ranges from 25% to 53%, with an average of 34%, which is generally below the stroke prevalence rates by sex (Tables 14 and15).…”
Section: Representation Of Women In Stroke Clinical Trialsmentioning
confidence: 99%
“…The proportion of female patients enrolled in the clinical trials investigated in this meta‐analysis is consistent with the female enrollment observed in other cardiovascular trials, especially in the field of electrophysiology. Trials investigating arrhythmia and more particularly devices or interventions have been shown to be particularly prone to underenrollment of women . Several reasons have been suggested in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…cancer, vascular surgery and cardiovascular trials 9, 10, 11, 12, 13), with the general media continuing to report that large gender gaps are still putting women at a disadvantage 14. This reporting has had serious effects on policy, with large amounts of money being allocated to study gender differences in healthcare 15.…”
Section: Introductionmentioning
confidence: 99%